Structural performance of concrete bridge decks reinforced with Grade-830 steel bars. (October 2020) - Kareem, Rahman S.; Jones, Casey; Dang, Canh N.; Prinz, Gary S.; Micah Hale, W.
Abstract: High-performance reinforcement, which is known by its high-corrosion resistance and high-strength, is advantageous in the design and construction of concrete bridge decks. This research investigates the structural behavior of concrete bridge decks reinforced with either high-performance A1035M (Grade 830) or ASTM A615M (Grade 420) reinforcing steel at both the service and strength limit states. The tensile strain of the reinforcing steel, the compressive strain of the concrete, and the deflection of the specimens were monitored continuously during testing. A crack width microscope was used to measure the maximum crack width and the number of cracks. The results indicated an increased serviceability and flexural strength for the decks containing Grade 830 reinforcing steel.